1977
DOI: 10.3758/bf03197390
|View full text |Cite
|
Sign up to set email alerts
|

Altering comprehension: The effect of biasing titles on text comprehension

Abstract: Titles can alter the comprehension of a text by affecting the selection of information from a text and the organization of this information in memory. Text comprehension is assumed to involve an organizational process that results in the formation of a text base, an ordered list of semantic units-propositions. The text base can be used as a retrieval scheme to reconstruct the text. Procedures for assigning propositions as more relevant to some themes as compared to other themes are developed and applied to tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
65
0
5

Year Published

1981
1981
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(73 citation statements)
references
References 14 publications
3
65
0
5
Order By: Relevance
“…These devices are used by writers to emphasize the structure of texts and to signal importance. Prior research has shown that readers' representation of the structure of narrative and expository texts is aided by signals that clarify the structure (Beck, McKeown, Sinatra, & Loxterman, 1991;Kozmnsky, 1977;Lorch & Lorch, 1995Lorch, Lorch, & Inman, 1993;Meyer & Rice, 1989;Millis & Just, 1994). This is especially true for challenging texts (Spyridakis & Standal, 1987) and for low-knowledge participants (Goldman, Saul, & Cote, 1995;Lorch & Lorch, 1996).…”
mentioning
confidence: 99%
“…These devices are used by writers to emphasize the structure of texts and to signal importance. Prior research has shown that readers' representation of the structure of narrative and expository texts is aided by signals that clarify the structure (Beck, McKeown, Sinatra, & Loxterman, 1991;Kozmnsky, 1977;Lorch & Lorch, 1995Lorch, Lorch, & Inman, 1993;Meyer & Rice, 1989;Millis & Just, 1994). This is especially true for challenging texts (Spyridakis & Standal, 1987) and for low-knowledge participants (Goldman, Saul, & Cote, 1995;Lorch & Lorch, 1996).…”
mentioning
confidence: 99%
“…The general strategy followed in this research was to construct texts with competing themes and manipulate the title of the text to emphasize one of the two themes, then observe the eff ects on ee recall. The fi nding om this research is that readers build a representation of the text that is organized around the biasing title (Bock, 1980;Kozminsky, 1977;Schwarz & Flammer, 1981) with the consequence that memory is better for content that is more closely associated with the theme emphasized by the biasing title than for content associated with the alternative theme. Similarly, Eyrolle, Virbel and Lemarié (2008) showed that users con onted with work documents containing titles that only partially refl ect the text content fail to identi topics that are not represented in the title.…”
mentioning
confidence: 99%
“…A second set of investigations used ee recall to understand how headings might infl uence readers' understanding of text (Bock, 1980;Kozminsky, 1977;Schallert, 1976;Schwarz & Flammer, 1981). The general strategy followed in this research was to construct texts with competing themes and manipulate the title of the text to emphasize one of the two themes, then observe the eff ects on ee recall.…”
mentioning
confidence: 99%
“…One such signal is a title for the passage. Kozminsky (1977), using passages with two alternate themes, found that recall was biased in favor of propositions relevant to the theme mentioned in the title. Another important surface-level signal is initial mention; items or ideas appearing first in a passage tend to be viewed as thematically important simply by virtue of their position .…”
mentioning
confidence: 99%